1989
DOI: 10.1172/jci113906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute ischemia in the dog on myocardial blood flow, beta receptors, and adenylate cyclase activity with and without chronic beta blockade.

Abstract: We ligated the left anterior descending coronary artery for 1 or 2 h in 31 purebred beagles. We did not detect any changes in ,8-adrenergic receptor density or affinity when normal and ischemic zones were compared, either in the subendocardium or in the subepicardium. In the ischemic zones, there was a significant decline in all measures of adenylate cyclase activity, including activity mediated by the ,-adrenergic receptor. By contrast, after chronic fl-adrenergic blockade (1.5 mg/kg propranolol i.v. twice da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…For example, a recent study (34) showed that propranolol, a nonselective /3-adrenergic receptor antagonist, resulted in increased net isoproterenol-stimulated cAMP production in ca- (1,34). Potential mechanisms underlying this alteration in adrenergic signaling include alterations in receptor number, in receptor-agonist affinity, or in receptor-Gsa coupling.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent study (34) showed that propranolol, a nonselective /3-adrenergic receptor antagonist, resulted in increased net isoproterenol-stimulated cAMP production in ca- (1,34). Potential mechanisms underlying this alteration in adrenergic signaling include alterations in receptor number, in receptor-agonist affinity, or in receptor-Gsa coupling.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, uncoupling of ,B, receptors may be the result of local ischemia (13,57), whereas decreased adenylate cyclase catalytic activity may be secondary to load-dependent tissue injury (45,46). These changes involving the powerful contractility-regulating receptor-G protein-adenylate cyclase pathway in the human heart indicate that this system has multiple potential regulatory sites, and the diversity of changes in different types of heart muscle disease illustrate the "model dependency" (9, 56) ofthe system.…”
Section: Discussionmentioning
confidence: 99%
“…The collateral-dependent region has normal function at rest, but, because of insufficient vascular reserve, has abnormal function when myocardial oxygen demands are increased. Important changes in myocardial f-adrenergic receptor (fAR)' expression have been found in animal models after complete coronary artery occlusion leading to myocardial infarction (3)(4)(5)(6)(7). In general, FAR upregulation is observed, a sequelae perhaps ofexternalization of cytosolic receptors previously sequestered by energy-dependent processes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found increased isoproterenol-stimulated adenylyl cyclase activity after acute severe myocardial ischemia (5), but most find decreased activity. Karliner et al (6) recently evaluated 3AR expression and adenylyl cyclase activity after 1-2 h of coronary occlusion in dogs. J3AR-mediated and stimulatory GTP-binding protein (Gs)-mediated cAMP production were 30-50% reduced in the ischemic regions of the left ventricle.…”
Section: Introductionmentioning
confidence: 99%